Analisa Hukum Kewenangan PPATK terhadap Kebijakan Pemblokiran Rekening Dormant Ditinjau dari Prinsip Fiduciary Duty Dalam Hubungan Bank dan Nasabah - Fabiola Nurul Oktavianingrum; Maria Ingrita Rindo Bupu (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study aims to conduct a legal analysis of the Financial Intelligence Unit (FIU) regarding the policy of blocking dormant accounts, examining it through the lens of the Fiduciary Duty Principle in the relationship between banks and their customers. The method used in this study is normative. Conducting an in-depth and comprehensive analysis through the provisions of laws and regulations that form the basis of the issue of blocking customer accounts, and also the regulations underlying the bank's obligations to its customers. Then, it was supported by other legal products during the analysis. The results of this study are that the FIU policy is a form of follow-up to the FIU's obligations and functions in Money Laundering Crimes. This policy also remains guided by the bank's duty to ensure legal certainty regarding the security, comfort, and trust of its customers. In addition, pursuant to Financial Services Authority Regulation Number 24 of 2025 concerning Account Management in Commercial Banks, banks are also required to supervise and report suspicious customer accounts. Banks are also required to provide information regarding the opening, use, and closure of their customer accounts